The Republic of Congo’s Infrastructure : A Continental Perspective - Pushak, Nataliya; Briceno-Garmendia, Cecilia M. (2012)
Infrastructure contributed half a percentage point to the Republic of Congo's annual per capita GDP growth from 2001 to 2006. If the country's infrastructure were improved to the level seen in Mauritius, the regional leader, it could contribute more than 3 percentage points to annual per capita growth. The Republic of Congo's existing infrastructure is concentrated in the developed south, reflecting the country's urbanization patterns. Links spread from there to the less-developed north, where there are vast areas of underexploited dense forest. The Republic of Congo's power sector offers the greatest potential for infrastructure-based economic growth, but major inefficiencies need to be addressed. Transit improvements would also make significant contributions to growth by improving connections to the north and to neighboring countries. Additional opportunities include rehabilitating the fixed-line telephone operator to spread Internet access. The country's water and sanitation infrastructure is in relatively good shape. Spending on infrastructure was $460 million per year in the Republic of Congo during the mid-2000s. Based on these spending levels, if all inefficiencies were eliminated, the country would face an infrastructure funding gap of $270 million a year and would not meet infrastructure targets for 31 years. Spending rose to $550 million per year in 2008-09. If the Republic of Congo could maintain these higher spending levels, the funding gap would essentially disappear. The nation could further reduce the funding gap by adopting lower-cost technologies to meet infrastructure targets.